Longevity of bonded composite restorations after dentin biomodification with neolignans obtained from Nectandra leucantha - Guedes, Mateus Henrique de Godoy; Maia, Marcelo Henrick Matochek; Graeff, Carlos Frederico de Oliveira; González, Alejandra Hortencia Miranda; Grecco , Simone dos Santos; D'Alpino, Paulo (Brazilian Dental Science, 2022)
Objective: This in vitro study evaluated the effect of neolignan-containing solutions on dentin biomodification previously applied to the bonding procedure in adhesive restorations. Material and Methods: Neolignans, dehydrodieugenol B–CP1 and dehydrodieugenol B methyl ether–CP2, were isolated from Nectandra leucantha and two aqueous solutions containing 0.13% neolignans, 0.2% propylene glycol and 3.0% ethanol were prepared. Bovine teeth were ground flat to obtain 2-mm thick specimens which received resin composite restorations (N=10). The neolignan solutions were applied before the bonding procedure (60 s). Experimental groups were: control, untreated group, 0.12% chlorhexidine gel, 0.13% CP1 solution, and 0.13% CP2 solution. A push-out bond strength test was conducted (0.5 mm/min). Bovine tooth sections (0.5×1.7×7.0 mm) were also obtained to assess the modulus of elasticity and mass change after treatment (N=15). A three-point bending test evaluated the elastic modulus of fully demineralized dentine beams after immersion in the solutions. The data were statistically analyzed (a = 0.05). Results: The bond strength of the restorations to dentin was significantly improved by the treatment with neolignan-containing solutions, irrespective of the evaluation time (p<0.05). After 6 months, a significant reduction in the bond strength was observed in the groups treated with the solutions (p>0.05), but the means were significantly higher than the control groups (p<0.05). The elastic modulus of demineralized dentin was significantly improved after the treatment with the solutions (p<0.05). All groups lost mass weight. Conclusion: The solutions improved the in vitro longevity of bonded restorations, possibly due to the dentin biomodification effect of the neolignans. KEYWORDS Dental restorations; Permanent; Dentin; Collagen type I; Plants medicinal; Lignans.